The Comedies of Alessandro Piccolomini: Searching for the Perfect Woman between Loving Initiative and Virtue - Martín-Clavijo, Milagro (Renaissance and Reformation / Renaissance et Réforme, 2023)
In theoretical works such as Orazione, Della institutione, and Raffaella, the Italian writer, scientist, and philogynist Alessandro Piccolomini (1508–78) outlines the characteristics that should make up the perfect woman. In his comedies—Alessandro and L’Amor costante—focusing mainly on the theme of love, Piccolomini presents some of the same ideas, articulating them through his noble and cultured female characters. This article examines Piccolomini’s dramatic productions in light of his treatises and other writings on women in order to underline his originality in the creation of these female characters. On the one hand, they are models of virtue and decorum; on the other, they demonstrate an unusual degree of initiative in love. They are conscious of their desires, and they defend their right to choose their lovers. In this way, Piccolomini describes new traits of the perfect woman.